Tinjauan Scoping Review: Efektivitas Media Edukasi Visual dan Audiovisual terhadap Perubahan Perilaku Kesehatan Gigi Mulut Lansia - Asterya Illa; Zahroh Shaluhiyah; Ayun Sriatmi (Jurnal Ners, 2026)
Background Oral health is an essential aspect of quality of life, particularly among older adults who are vulnerable to various oral health problems. However, their level of knowledge and behavior in maintaining oral hygiene remains relatively low. Objective This study aimed to examine the effectiveness of audiovisual media in promoting oral health among older adults. Method Participants were elderly individuals who received oral health education through audiovisual materials, including short videos demonstrating proper oral hygiene practices, the importance of regular dental check-ups, and the impact of oral health on overall well-being. Results The results indicated a significant improvement in oral health knowledge among older adults after receiving audiovisual education. Participants demonstrated better understanding of proper tooth brushing techniques, the importance of dental visits, and the use of oral hygiene aids. Conclusion Preventive health service utilization among informal workers is influenced by a combination of individual, audiovisual media is an effective educational tool to enhance knowledge, attitudes, and oral health behaviors among older adults. By engaging multiple senses in the learning process, audiovisual education improves information retention, motivation, and consistency in healthy practices. Keywords: informal workers, preventive health, determinants, social security, health access